Combined Oral and Topical Application of Pumpkin (Cucurbita pepo L.) Alleviates Contact Dermatitis Associated With Depression Through Downregulation Pro-Inflammatory Cytokines - Balgoon, Maha Jameal; Al-Zahrani, Maryam H.; Jaouni, Soad Al; Ayuob, Nasra (Frontiers in Pharmacology, 2021)
Background: Depression and contact dermatitis (CD) are considered relatively common health problems that are linked with psychological stress. The antioxidant, anti-inflammatory, and antidepressant activities of pumpkin were previously reported. Objectives: This study aimed to evaluate the efficacy of the combined topical and oral application of pumpkin fruit (Cucurbita pepo L.) extract (PE) in relieving CD associated with chronic stress–induced depression and compare it to the topical pumpkin extract alone and to the standard treatment. Materials and Methods: Forty male albino rats were exposed to chronic unpredictable mild stress (CUMS) for 4 weeks for induction of depression and then exposed to (1-fluoro-2, 4-dinitrofluorobenzene, DNFB) for 2 weeks for induction of CD. Those rats were assigned into 4 groups (n = 10 each); untreated, betamethasone-treated, PE-treated and pumpkin extract cream, and oral-treated groups. Treatments were continued for 2 weeks. All groups were compared to the negative control group (n = 10). Depression was behaviorally and biochemically confirmed. Serum and mRNA levels of pro-inflammatory cytokines, such as TNF-α, IL-6, COX-2, and iNOS, were assessed. Oxidant/antioxidant profile was assessed in the serum and skin. Histopathological and immunohistochemical assessments of affected skin samples were performed. Results: Pumpkin extract, used in this study, included a large amount of oleic acid (about 56%). The combined topical and oral administration of PE significantly reduced inflammatory and oxidative changes induced by CD and depression compared to the CD standard treatment and to the topical PE alone. PE significantly alleviated CD signs and the histopathological score (p < 0.001) mostly through the downregulation of pro-inflammatory cytokines and the upregulation of antioxidants. Conclusion: Pumpkin extract, applied topically and orally, could be an alternative and/or complementary approach for treating contact dermatitis associated with depression. Further studies on volunteer patients of contact dermatitis are recommended.